(untitled) (Journal of Information Systems and Technology Management, 2007)
Business executive are rethinking business concept, based on horizontalization principles. As so, most organizational functions are outsourced, leading the enterprise to build business through a network of organizations. Here we study the case of Cia Hering's network of organizations, a leader in knit apparel segment in Latin America (IEMI, 2004), looking at the network's structure and levels of cooptation. A theoretical model was used using Quinn et al. (2001) "sun ray" network structure as basis to analyze the case study. Main results indicate higher degree of structural conformity, but incipient degree of coopetation in the network.